Semantic transformation of economic-financial Latin loanwords in Uzbek official documents - Juraev, Shohruh Bakhtiyorovich (The Lingua Spectrum, 2026)
This article examines the semantic transformation of Latin-based loanwords related to the economic and financial sphere in Uzbek official documents. The relevance of the study is determined by the need to analyze lexical and semantic changes taking place in the Uzbek language under the influence of globalization, international economic relations, financial regulation, and modern terminological development. The theoretical framework of the article is based on E. Haugen’s approach to linguistic borrowing, E.C. Traugott and R.B. Dasher’s theory of semantic change, and A. Blank’s cognitive typology of motivations for the emergence of new meanings. The empirical material consists of seven presidential decrees and resolutions issued between 1991 and 2025 in the field of economics and finance. The study combines statistical, etymological, semantic, and contextual methods of analysis. The frequency analysis demonstrates a gradual increase in the use of Latin-rooted loanwords in Uzbek official documents, especially in the most recent five-year period. Particular attention is paid to such lexical units as balans, eksport, import, inkubator, komissiya, kompensatsiya, sanksiya, and tendensiya. The article analyzes their origin, paths of borrowing, adaptation into Uzbek, and semantic development in official discourse. The findings show that most of these lexical units entered Uzbek through Russian mediation and are used mainly in denotative, terminological, and normative meanings. The study concludes that Latin loanwords play an important role in the formation, modernization, and functional expansion of economic and financial terminology in Uzbek official language.